2008
DOI: 10.1179/174367508x306532
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of bioactive and antibacterial glass–ceramic Part 1 – Microstructure, properties and biological behaviour

Abstract: Synthesis and characterisation of bioactive and antibacterial glass-ceramic Part 1 -Microstructure, properties and biological behaviour / E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Afterwards, some bacterial colonies were spread in normal saline (0.9% P/V of NaClin distilled water) to obtain a standard 0. plate. The number of dilution was chosen on the basis of previous works [18,19]. The blood-agar plates were incubated at 35°C and after 24 h, the CFU were counted; the obtained number was multiplied by the dilution factor in order to get the total number of CFU of the starting solution.…”
Section: Antibacterial Testsmentioning
confidence: 99%
“…Afterwards, some bacterial colonies were spread in normal saline (0.9% P/V of NaClin distilled water) to obtain a standard 0. plate. The number of dilution was chosen on the basis of previous works [18,19]. The blood-agar plates were incubated at 35°C and after 24 h, the CFU were counted; the obtained number was multiplied by the dilution factor in order to get the total number of CFU of the starting solution.…”
Section: Antibacterial Testsmentioning
confidence: 99%
“…The same timetable in terms of bioactivity was observed for CEL2 scaffolds . Then, the presence of silver does not influence the bioactivity mechanism and kinetics, as already observed in previous works …”
Section: Discussionmentioning
confidence: 94%
“…11 Then, the presence of silver does not influence the bioactivity mechanism and kinetics, as already observed in previous works. 10,32 Leaching tests showed that silver was released with kinetics helpful to treat both the development of infections due to bacterial contamination (direct or indirect) of an implant throughout the surgery and the development of latent infections. Moreover, the total amount of silver released (about 0.035 mg) is extensively below the values that are considered toxic for healthy cells (about 0.1 mg for L929 fibroblasts).…”
Section: Discussionmentioning
confidence: 99%
“…In this work the bioactive and ferrimagnetic SC45 was enriched with silver to impart antimicrobial properties, thus realizing a multifunctional glass-ceramic useful for the treatment of bone tumor and associated complications. Since it was already demonstrated by the authors that the introduction of a small amount of silver does not inhibit the bioactive behavior of a glass/glass-ceramic, or at least it can improve bioactivity [28,29,35,36], in this work the influence of the Ag introduction in the glass-ceramic composition was principally investigated in terms of structure, morphology, magnetic and antibacterial properties. The obtained glass-ceramic could be proposed as filler in polymeric-based bone cement or in other injectable materials for bone surgery that need to be improved with bioactive, magnetic and antibacterial properties by the presence of a single additional phase.…”
Section: Introductionmentioning
confidence: 99%